The role of dietary polyphenols in patients with rheumatoid arthritis – a review of literature - Dojs, Adriana; Roś, Bartosz; Siekaniec, Katarzyna; Kuchenbeker, Natalia; Mierzwińska-Mucha, Julia; Jakubowicz, Magdalena (Journal of Education, Health and Sport, 2025)
Introduction and purpose: Rheumatoid arthritis (RA) is a systemic, autoimmune disease of the connective tissue, affecting predominantly symmetrical synovial joints. RA is characterized by a complex, multifactorial etiology, including genetic and environmental factors, the latter of which have been scrutinized in the recent years. One of the modifiable factors affecting the disease is diet. The purpose of this review is to present current data on the role of polyphenols in diet in patients with RA. A brief description of the state of knowledge: The etiology of rheumatoid arthritis includes genetic predispositions along with environmental factors – such as diet. There have been numerous studies analysing different types of diet and particular compounds which may alleviate disease activity in patients and lower its burden. However, currently there are no standardised recommendations proposed for physicians, or patients regarding the advised dietary measures. Polyphenols are natural compounds found in plants which have been frequently investigated for their anti-inflammatory properties and impact on autoimmune disorders. Studies have found that some polyphenols, such as curcumin, resveratrol, quercetin, and more, lower the disease activity score (DAS-28) in patients with RA, or lighten reported symptoms, by interacting with several pathways of the disease and attenuating oxidative stress. Summary: RA is an autoimmune disorder, affecting increasingly more patients. The burden of the disease is paramount, thus encouraging research into beneficial methods of conventional and adjuvant treatment. Diet is one of the crucial focal points for further exploration. Current data provide promising evidence on the effects of polyphenols on RA activity but further research, especially clinical trials, is required.